Communication Between Parents and Adolescents: Its Influence on Adolescent’s Enjoyment and Flow - Raimundi, María Julia; Molina, María Fernanda; Leibovich de Figueroa, Nora; Schmidt, Vanina (Revista de Psicología, 2017)
The aim of this work was to study the influence of adolescent-parents communication in enjoyment and optimal experiences (flow) in adolescents’ activities. Adolescents (n = 159) of both genders (37.7% males; M age = 14.7, SD = 1.7) from three public schools in Buenos Aires, Argentina participated in the study. Pearson correlations, simple and multiple linear regressions, and logistic regressions were performed. Results showed that positive communication with both parents (more open and less problematic) predicted enjoyment and time spent in structured activities, such as sports or artistic activities. Lower levels of problems in communication with the father predict more time spent on social activities. These results are discussed in terms of the importance of communication with both parents for the enjoyment and optimal flow experience in adolescents’ activities.